Lung Abscess Case Series and Review of the Literature - Lamees Yousef; Abdullah Yousef; Abdullah Al-Shamrani (MDPI AG, 2022)
(1) Background: Lung abscess is a lung infection that leads to the destruction of the lung parenchyma, resulting in a cavity formation and central necrosis filled with purulent fluids. It is an uncommon pediatric problem, and there is a paucity of literature reviews on this subject, especially for the pediatric age group. Lung abscess is commonly divided into those considered primary in previously well children or secondary in those with predisposing co-morbidities. The predominant pathogens isolated from primary lung abscesses are the aerobic organisms, including streptococcal species, Staphylococcus aureus, and Klebsiella pneumoniae, while anaerobic bacteria such as Bacteroides species are predominant in secondary groups. Children usually present with fever, cough, shortness of breath, chest pain, and sputum. While physical examination may reveal diffuse crackles on auscultation, the diagnosis is usually confirmed by chest X-ray. (2) Methods: We report four different cases with lung abscesses from both primary and secondary group with similar presentations and radiological findings, but the approach was different in each according to the underlining cause. (3) Conclusions: Conservative therapies with a prolonged course of antibiotics remain the cornerstone of therapy for both primary and secondary lung abscesses. The underlying cause should be considered when there is a suboptimal response. However, invasive intervention is becoming more popular with better yield, shorter duration of antibiotics and admission, and excellent prognosis.